Análisis del proceso contable y su incidencia en los estados financieros de la empresa Contaxmachaleñita S.A. de Machala. - Alulima Capa, Esther Dalila (2017)
The Work of Titulación ANALYSIS OF THE ACCOUNTING PROCESS AND ITS INCIDENCE IN THE FINANCIAL STATEMENTS OF THE COMPANY CONTAXMACHALEÑITA S.A. DE MACHALA, is composed of four chapters the same that are detailed below: CHAPTER I: GENERALITIES OF THE STUDY OBJECT, Definition and contextualization describes the problem of research through the object of study and the Contextualization. Interesting Facts detail the problem of the company detail the causes and effects of the problem raised and Justification is the importance of the development of this research topic, and we set the general and specific objectives of the research. CHAPTER II: THEORETICAL BACKGROUND: Description of the epistemological approach of reference, It describes the investigative antecedents that support the present study and the legal foundation helps us to support the credibility of the information presented in the present work. Additionally it establishes the theoretical bases of the investigation where it exposes the basic concepts of: Accounting rules establishes principles and norms for the presentation of the financial statements, accounting is a technique that helps to register, classify, and summarize the mercantile operations, process Accountant is the steps to follow in an accounting year, chart of accounts is the numbering of accounts in an orderly manner, assets are assets owned by the company, liabilities liabilities of the company, equity capital of the company, income are the Increments of the company, costs are disbursements made by the company for the production of products, expenses are decreases in equity, initial status is the accounting document that reflects the situation of the company, opening seat is the seat that opens The new journal, daily book is where the annotations are written, accounting adjustments are the income or expenses that have not been registered for any reason, the greater general is the registration of each account to know their actual balances, checking balance, financial statement , Statement of income, statement of financial position, cash flow statement, statement of changes in equity, and notes clarifying the same that would help a better understanding of the problem. CHAPTER III: METHODOLOGICAL PROCESS: Design or tradition of the research selected in which the basic modality of the research is described is the way in which the information will be acquired for the present study, and the feasibility analysis of the research describes that It is as feasible to be the research, in the process of writing data is written the research tools for writing data, also explains the system of categorization in data analysis where we explain the tools we apply to research such as Guide of observation and interview to the accounting staff, these instruments allowed to know the problematic of the company, also we described the tables of questions and statistical graphs. CHAPTER IV: RESULTS OF THE INVESTIGATION: The description and theoretical argumentation of results are detailed, a brief analysis of the results of the research is detailed. Conclusions describes the analysis of the research results and in the recommendations we detail the measures that the company should adopt based on the results of the research.